Pengaruh Aset Pajak Tangguhan, Beban Pajak Tangguhan Dan Perencanaan Pajak Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Makanan & Minuman Yang Terdaftar di BEI Tahun 2017-2021) - Adella Delvi Foan Olin; Eko Sasongko Priyadi (CV. ITTC INDONESIA, 2024)
This study aims to examine the effect of deferred tax assets, deferred tax burden and tax planning on earnings management. The object of this study is food & beverage companies listed on the Indonesia Stock Exchange in the period 2017-2021. The research method used in this study is a descriptive research method with a quantitative approach. The sampling technique used is purposive sampling. Based on the predetermined criteria, 11 food & beverage companies listed on the Indonesia Stock Exchange for the period 2017-2021 were obtained. The data analysis techniques used in this study are descriptive statistical analysis, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple regression test, determination coefficient test, t-statistic test and f-statistic test. The results of this study indicate that deferred tax assets have a negative effect on earnings management. Then deferred tax burden has a positive effect on earnings management. While tax planning has an effect on earnings management.